Antioxidant response versus selenium accumulation in the liver and kidney of the Siberian sturgeon (Acipenser baeri) - N. Pacini; A. Elia; M. Abete; A. Dörr; P. Brizio; M. Righetti; M. Prearo; GASCO, Laura (Chemosphere, 2013)
The aim of this study was to examine the effects of selenium on concentrations of metabolites and enzyme activities acting as antioxidant markers in liver and kidney of Siberian sturgeon Acipenser baeri. Sturgeons were fed selenium cysteine for 30 and 60d at 1.25, 5, 20mg Sekg-1. Selenium level in the control feed was 0.32mgkg-1. Se concentration was measured in liver, kidney and muscle of every specimen. Sturgeon accumulated Se in tissues with a clear dose-response relationship and the highest Se concentration was recorded in liver. This outcome is lined up with the findings obtained on the antioxidant markers evaluated in both tissues, and in which a dose-response for several biomarkers was recorded in liver. The superoxide dismutase activity in Se-treated fish was generally induced, while catalase activity was lower in liver or unaltered in kidney. The concentrations of glutathione S-transferase, glutathione reductase and total glutathione responded differently for both tissues and were induced in a different way at both endpoints. No changes of glyoxalase I activity were noted for both Se-treated tissues, while for glyoxalase II enzyme in liver a dose-related pattern was found showing a reversible effect (decreased and increased counteractive response) only in the 5mgkg-1 group. Moreover, the highest Se concentrations did not cause marked changes in malondialdehyde levels of liver and kidney. The enhancement of glutathione peroxidase activity in Se-treated sturgeon might have prevented the lipid peroxidation in both tissues, providing to the Siberian sturgeon a great defense ability versus the prooxidant effect of selenium. © 2013 Elsevier Ltd.